Pengaruh Metode Outbond terhadap Kemampuan Berpikir Kreatif Kelompok B Gugus I Kecamatan Sawan - Cahyani, Gita Restu; Tegeh, I Made; Magta, Mutiara (Jurnal Pendidikan Anak Usia Dini Undiksha, 2020)
This study aimed at determining the significant differences in creative thinking abilities between groups that were given an outbound training method and the groups that were given an expository learning in children of group B in Gugus I Kecamatan Sawan in academic year 2019/2020. This study used a quasi-experimental research design with pre-test and post-test control group design. The population of this study were all children of Group B in Gugus I Kecamatan Sawan with a total of 208 children. The sampling technique used in this study was a random sampling technique. The sample in this study were the children of group B in TK Widya Sesana Desa Sangsit consisted of 26 children as an experimental group who were given learning by using an outbound training method. Meanwhile, the children of B group in TK Tujuh Belas Agustus Desa Bungkulan consisted of 25 children were as a control group who were given learning by using an expository learning strategy.The data on children's creative thinking abilities were collected by observation and interview techniques which were analyzed using descriptive statistical analysis and inferential statistics, namely t-test. Based on the results of data analysis showed that the tcount is 27.19 and ttable with a significance level of 5% and dk = 49 is 2.01. The results indicated that tcount>ttable, the average post-test result of the experimental group is 50.65 and the average post-test result of the control group is 42.56, meaning that the average results of the experimental group> the average results of the control group. The results showed that there are significant differences in creative thinking abilities between groups that were given an outbound learning method and the groups that were given expository learning in children of group B in Gugus I Kecamatan Sawan in academic year 2019/2020. Keywords: creative thinking abilities, outbound training, early childhood children